Induction of ALP and MMP9 activity facilitates invasive behavior in heterogeneous human BMSC and HNSCC 3D spheroids. Issue 11 (31st July 2019) - Wessely, Anja; Waltera, Anna; Reichert, Torsten E.; Stöckl, Sabine; Grässel, Susanne; Bauer, Richard J.
Abstract : Mesenchymal stem cells (MSCs) are multipotent progenitor cells capable of differentiating into adipocytic, osteogenic, chondrogenic, and myogenic lineages. There is growing evidence that MSCs home into the tumor microenvironment attracted by a variety of signals such as chemokines, growth factors, and cytokines. Tumor‐homing stem cells may originate from bone marrow–derived MSCs (BMSCs) or adipose tissue‐derived MSCs. Recent scientific data suggest that MSCs in combination with tumor cells can either promote or inhibit tumorigenic behavior. In head and neck squamous cell carcinoma (HNSCC), BMSCs are reported to be enriched with a potential negative role. Here, we evaluated the effect of BMSCs from 4 different donors in combination with 4 HNSCC cell lines in a 3‐dimensional multicellular spheroid model. Heterogeneous combinations revealed an up‐regulation of gene and protein expression of osteogenic markers runt‐related transcription factor 2 (RUNX2) and alkaline phosphatase (ALP) together with a substantial secretion of matrix metalloproteinase 9. Moreover, heterogenous BMSC/tumor spheroids showed increased invasion compared with homogenous spheroids in a Boyden chamber invasion assay. Furthermore, inhibition of ALP resulted in a substantially decreased spreading of heterogeneous spheroids on laminin‐rich matrix. In summary, our data suggest a prometastatic effect of BMSCs combined with HNSCC.—Wessely, A., Waltera, A., Reichert, T. E., Stöckl, S., Grässel, S., Bauer, R. J. Induction of ALP and MMP9 activity facilitates invasive behavior in heterogeneous human BMSC and HNSCC 3D‐spheroids. FASEB J. 33, 11884–11893 (2019). www.fasebj.org